An Examination of the Interactions of Race and Gender on Sentencing Decisions Using a Trichotomous Dependent Variable. (February 2013) - Freiburger, Tina L.; Hilinski, Carly M.
This study examined how race, gender, and age interact to affect defendants' sentences using a trichotomized dependent variable. The findings indicate that the racial and gender disparity found in sentencing decisions was largely due to Black men's increased likelihood of receiving jail as opposed to probation. The results also show that being young resulted in increased odds of receiving probation over jail for White men and for women but resulted in decreased odds for Black men. Separate analysis of incarceration terms to jail and prison further reveal that legal factors had a greater impact on prison than on jail sentence length. Overall, the results strongly support the argument that sentencing research needs to consider sentences to jail and prison separately.